Efficacy of Neem Extract and Three Antimicrobial Agents Incorporated into Tissue Conditioner in Inhibiting the Growth of C. Albicans and S. Mutans - Dikshita Ray Barua; Jayaprakash Mugur Basavanna; Rana Kalappattil Varghese (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Denture stomatitis is an inflammatory condition which compromises the mucosal surface beneath dentures. The aetiology of denture stomatitis is usually multifactorial which varies from trauma from ill fitting denture to poor immune system. There are evidences that denture stomatitis is an outcome of multispecies biofilms that include Candida albicans and Streptococcus mutans. Tissue conditioners are found to be more susceptible to colonisation by micro-organisms. Aim: The purpose of this study was to compare the efficacy of neem leaf extract and three other antimicrobial agents incorporated in a tissue conditioner against both Candida albicans and Streptococcus mutans. Materials and Methods: Standard strain of Candida albicans and Streptococcus mutans were inoculated into Sabouraud Dextrose broth and Mitis-Salivarius-Bacitracin broth respectively incubated at 37°C. Tissue conditioner (Viscogel) mixed with two different concentrations of ketoconazole, nystatin and chlorhexidine diacetate (5%, 10% w/w) and neem leaf extract (7.5% w/w and 15% w/w) and control group (plain tissue conditioner) were placed into punch hole (6 mm diameter) agar plate inoculated with Candida albicans and Streptococcus mutans. A total of 216 samples were prepared for both Candida albicans and Streptococcus mutans. Mean Inhibition Diameter (MID) across each punch holes were measured in millimetres at 24 hours and seven days and data were statistically analysed using Kruskal Wallis test followed by Mann-Whitney U test. Results: Both ketoconazole and nystatin (10% w/w) showed maximum inhibition of 32 mm and mean of 31.75 followed by 15% w/w neem leaf extract with an inhibition of 21 mm and mean of 20.67 after 24 hours against Candida albicans whereas chlorhexidine diacetate (10% w/w) showed mean of 25.67 followed by chlorhexidine diacetate (5% w/w) and neem extract (15% w/w) which showed mean of 24.17 and 23.67 respectively against Streptococcus mutans. Conclusion: Neem leaf extract exhibited considerable potential to be an efficacious antimicrobial agent against both Candida albicans and Streptococcus mutans.